The Effect of Injection Parameters on Warpage, Shrinkage, and Tensile Strength of Polypropylene Composites - Andre Bawono, Julius; Budiarto; Kurniawan, Perwita (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
Polypropylene composite material is an environmentally friendly material when compared to other polymer materials because the composition of polypropylene is only 76% and the remaining 24% is limestone. The use of this composite material is to reduce dependence on the use of Acrylonitrile Butadiene Styrene (ABS) and Acrylic Styrene (AS) resins because both materials are difficult to decompose and recycle. The